2014
DOI: 10.5099/aj140100032
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Toxicological Profile of Ibuprofen in Wistar Albino Rats

Abstract: Ibuprofen is an effective, cheap, and frequently used non-steroidal anti-inflammatory drug. The present study investigated the dose-and time-dependent effects of ibuprofen on hepatic, renal, and hematological functions in rats. Groups of rats (n=6) were given ibuprofen (20, 40 mgkg -1 day -1 ) for 7, 14 or 28 days; or vehicle (control), orally. Blood samples were obtained, and hematological indices and biochemical markers of hepatic and renal functions were measured. Ibuprofen significantly increased, P < 0.00… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
15
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 26 publications
3
15
1
1
Order By: Relevance
“…Adverse effects following aspirin administration in normal rats might be an outcome of NSAIDs induced inhibition of prostaglandin synthesis which leads to renal vasoconstriction and decreased renal perfusion which is responsible for acute renal abnormalities [ 28 – 30 ]. Aspirin-induced liver toxicity is obvious, as liver is the major target organ for drug metabolism and hepatic biotransformation reactions are known to induce apoptosis of hepatocytes [ 31 ]. Furthermore, aspirin-induced liver toxicity could be an outcome of idiosyncratic metabolic reaction due to aberrant metabolism of the drug where accumulation of toxic metabolites in hepatocytes binds to cell proteins and leads to abnormalities [ 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Adverse effects following aspirin administration in normal rats might be an outcome of NSAIDs induced inhibition of prostaglandin synthesis which leads to renal vasoconstriction and decreased renal perfusion which is responsible for acute renal abnormalities [ 28 – 30 ]. Aspirin-induced liver toxicity is obvious, as liver is the major target organ for drug metabolism and hepatic biotransformation reactions are known to induce apoptosis of hepatocytes [ 31 ]. Furthermore, aspirin-induced liver toxicity could be an outcome of idiosyncratic metabolic reaction due to aberrant metabolism of the drug where accumulation of toxic metabolites in hepatocytes binds to cell proteins and leads to abnormalities [ 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Aspirin-induced liver toxicity is obvious, as liver is the major target organ for drug metabolism and hepatic biotransformation reactions are known to induce apoptosis of hepatocytes [ 31 ]. Furthermore, aspirin-induced liver toxicity could be an outcome of idiosyncratic metabolic reaction due to aberrant metabolism of the drug where accumulation of toxic metabolites in hepatocytes binds to cell proteins and leads to abnormalities [ 30 , 31 ]. Observations made on total protein levels are in accordance with this fact.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings are in agreement with the previous studies done by Garba et al (2012) in which plasma ASTand ALT activities showed significant increasein the ibuprofen (100mg/kg) treated rats.The reduction in transaminases may be due to tissue damage, alterations of the permeability of cell membrane (Farage et al, 2010). Aprioku et al (2014) studied the effects of ibuprofen (20 and 40 mg/kg) on hepatic, renal, and hematological indices in relation to dose and duration of exposure. They reported that the elevation in serum levels of alanine transaminase (ALT) and alkaline phosphatase (ALP) by ibuprofen in their study was indicative of cellular injury to the liver.…”
Section: Discussionmentioning
confidence: 99%
“… 3 Diclofenac acts on decreasing the prostaglandin synthesis through inhibition of cyclooxygenase enzymes and diminishing the apoptosis. 4 , 5 Diclofenac induces hepatotoxicity and renal toxicity as a side effect. 2 , 6 It is known that anti-inflammatory drugs badly affect reproduction.…”
Section: Introductionmentioning
confidence: 99%